Pengaruh Konflik Kerja dan Konfil Keluarga terhadap Kinerja Karyawan - Adetya, Sandra (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Work-family conflict is a common issue faced by employees across various sectors, which can significantly impact their performance. This conflict arises when the demands of work and family collide, creating tension and stress that affect psychological well-being and productivity. Therefore, it is crucial to understand the relationship between work-family conflict and its effects on employee performance, as well as explore ways to manage and mitigate this conflict. This study aims to analyze the influence of work conflict and family conflict on employee performance by referring to relevant theories and previous research, and to provide recommendations for organizations in managing this conflict. This research utilizes a literature review method by examining relevant national and international journals and previous studies from the past five years. Data was collected through content analysis of articles discussing work-family conflict and its impact on performance, as well as policies to reduce its negative effects. The findings show that work-family conflict significantly affects employee performance by increasing stress, fatigue, and reducing productivity. Theories such as Role Theory and Conservation of Resources Theory explain how conflicts between work and family roles deplete individual resources, leading to decreased performance. Additionally, policies supporting work-life balance, such as flexible working hours, social support, and wellness programs, have been proven to effectively mitigate the negative impact of this conflict.